Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/ncomms7247
|View full text |Cite
|
Sign up to set email alerts
|

Cracking-assisted photolithography for mixed-scale patterning and nanofluidic applications

Abstract: Cracks are observed in many environments, including walls, dried wood and even the Earth's crust, and are often thought of as an unavoidable, unwanted phenomenon. Recent research advances have demonstrated the the ability to use cracks to produce various micro and nanoscale patterns. However, patterns are usually limited by the chosen substrate material and the applied tensile stresses. Here we describe an innovative cracking-assisted nanofabrication technique that relies only on a standard photolithography pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
106
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 29 publications
1
106
0
Order By: Relevance
“…Generating controllable cracks has been reported before . The single crack in our work is obtained by strategically positioning stress focusing V‐notch features.…”
Section: Resultsmentioning
confidence: 99%
“…Generating controllable cracks has been reported before . The single crack in our work is obtained by strategically positioning stress focusing V‐notch features.…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, Kim et al reported an alternative technique for fabricating PDMS nanofluidic devices based on another type of materials failure—cracks . Cracks are often considered unfavorable especially in micro‐/nanofabrication, but have been actively utilized to form micro‐/nanopatterns sometimes.…”
Section: Materials and Methods For Fabricating Nanofluidic Devicesmentioning
confidence: 99%
“…g) Fluidic transport in the nanochannels is confirmed by introducing a solution of fluorescein isothiocyanate (FITC). Reproduced with permission . Copyright 2015, Nature Publishing Group.…”
Section: Materials and Methods For Fabricating Nanofluidic Devicesmentioning
confidence: 99%
“…However, some examples of nanofluidic experiments were performed in extremely simple bottom‐up synthesized structures. These include nanochannels obtained by exploiting the cracking patterns of polymers upon tensile stresses, unorganized nanoporous matrices, inorganic, carbon nanotube membranes and hollow nanowire arrays . Although these methods are very affordable they still have some major drawbacks.…”
Section: Introductionmentioning
confidence: 99%